Students' Creative Thinking Ability Through Open-Ended Problem Learning - Erprabowo, Alfian; Caswita, Caswita (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
One of the elements affecting students' success rates in the learning process is their capacity for mathematical creativity. According to survey findings, pupils still have a limited capacity for mathematical creativity in their learning, as evidenced by the markers of this capacity. This study sought to ascertain how adopting open-ended problem learning models affected students' mathematical and creative thinking skills. This study employs quantitative research and descriptive methodologies. This study employed a research design was quasi-experimental research. The investigation employed a posttest-only control group design. Students in class VII made up the study's population. Class VIIb and VIIc samples were used in this study. Class VIIc serves as the control class and follows a traditional learning approach while Class VIIb serves as the experimental class. Research strategies for gathering data take the shape of tests. t-test data analysis formula. Based on the one-sided test calculation results, it can be seen that the average mathematical creative thinking ability of students using the Open-Ended Problem learning model is higher than the average mathematical creative thinking ability of students using conventional learning models, meaning that there is an influence using the Open-Ended Problem learning model on students' mathematical creative thinking abilities. The study's overall conclusion is the Open-Ended Problem learning approach has an impact on students' mathematical and creative thinking skills.